Learning Guidance For Children With Difficulties Learning To Read Class II At Sd Miftahul Ulum Menganti (Case Study) - Nita Andriani; Nataria W. Subayani, M.Pd (International Journal of Technology and Education Research, 2023)
This research is supported by the presence of students who have difficulty learning to read. So that the researchers studied in depth the problems of learning to read that occurred in research subjects who were class II students at SD Miftahul Ulum Menganti, Gresik Regency.This research is a qualitative research with the form of case study research which was conducted on only two subjects, namely AR and KK. The subjects in this study were students of class II SD Miftahul Ulum, Gresik Regency. The data collection techniques used were observation, interview and documentation. Based on the results of the research and discussion, it can be concluded that the learning difficulties that arise in the subject (AR and KK) are not being able to read, not memorizing the alphabets, not being careful in writing, so they often write wrong words or sentences. The cause of AR experiencing learning difficulties is due to the busyness of parents so that AR feels that there is no one accompanying learning, the lack of time limits for playing so that AR often forgets time to forget the time to study. Meanwhile for KK, there is a lack of curfew for studying and no tutors when studying so that KK feels lazy to study because there is no one to accompany them.